Alternatives for Latin American Integration: Beyond Racial Fusion and Multiculturalism. (March 2018) - Granada-Cardona, Juan Sebastián
Latin American integration is a core issue in Rodolfo Stavenhagen's "Seven Erroneous Theses about Latin America." A critical reading of the sixth thesis suggests an alternative interpretation. Changes in the past 50 years with regard to Latin American ethnic integration, for example in Mexico and Colombia, have called into question the model of integration through assimilation. The current challenges to integration in Latin America point to an alternative approach that attributes positive value to hybrid status as a path toward overcoming internal colonialism. La integración latinoamericana es un tema fundamental en las "Siete tesis equivocadas sobre América Latina" de Rodolfo Stavenhagen. Una lectura crítica de la sexta tesis sugiere una interpretación alternativa. En los últimos 50 años, los cambios relacionados con la integración étnica de América Latina (por ejemplo, en los casos de México y Colombia) han cuestionado el modelo de integración por asimilación. Los retos actuales a la integración regional apuntan hacia un enfoque alternativo que, buscando abrir caminos para superar el colonialismo interno, otorga un valor positivo al estatus híbrido.